PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH DARAH KABUPATEN/KOTA (STUDI EMPIRIS KABUPATEN/KOTA DI PULAU SUMATERA) - Maiyora, Gita; -, Yusrarlaini; Natariasari, Rizka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to demonstrate empirically the effect caused by the variable size, wealth, the size of local government leglislatif, leverage and intergovernmental revenue effect with the financial performance of local government regency/municipal in Sumatra Island. This study uses purposive sampling with 83 samples obtained from regency/municipal in Sumatera Island. Data analysis techniques used in this study is multiple regression analysis with SPSS 16. The results showed that the regression equation indicates that the variable size has a positively significant effect to the financial performance where the significant value are 0,005 < 0,05 and value of tcount > ttable 2.862 >1.992. and variable intergovermental revenue has positive value and significant impact on financial performance where the significant value are 0,000 < 0,05 and value of tcount > ttable 5.279>1.992. While the variable wealth and the size of the legislature (DPRD) has not significant influence to the financial performance of the region with significance greater than 0.05.Keywords: size, wealth, the size of the legislature, leverage, intergovernmental revenue, financial performance of local government